Memellanders in Norway after World War 2 - Ludvigsen, David Sætre (Genocidas ir rezistencija, 2024)
In the aftermath of World War II, a group of 843 individuals from the area that today constitutes Lithuania found themselves stranded in Norway. Included among them were a number of people from the formerly German Memel region (Klaipėdos kraštas). As repatriation efforts commenced in 1945, the Western Allies made a distinction between Lithuanians and Memellanders in such a way that it directly impacted where each individual could settle after the war. Lithuanians were offered to either go home, or to resettle in the West, while Memellanders on the other hand primarily were repatriated to Germany. This decision forced individuals to weigh their personal identities against practical considerations. In this situation, some individuals aligned with their true nationality while others made more pragmatic choices based on what they saw as the most favourable outcome. This article explores the situation of the Memellanders in Norway during the war, and the circumstances surrounding their repatriation.